2020
DOI: 10.1155/2020/8833828
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and Antihypertensive Properties and Safety for Use of Annona muricata and Persea americana and Their Combination Products

Abstract: Introduction. In the management of hypertension (a cardiovascular disease and the leading metabolic risk factor in noncommunicable diseases) with herbal medicines, efficacy and safety are of uttermost concern. This study sought to establish hypotensive, antihypertensive, drug interaction, and safety for use of the aqueous leaf extracts of Annona muricata (AME), Persea americana (PAE), or their combination products (CAPE). Methodology. Systolic and diastolic blood pressure (SBP and DBP), mean arterial blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…pilosa and C . citratus , bioactive compounds present such as the phytochemicals mainly flavonoids and phenolic compounds act synergistically to cause a reduction in cardiac output and/or total peripheral resistance and consequently a decrease in blood pressure [ 39 ]. These effects would therefore be one of the mechanisms by which the aqueous extract of the mixture exerts its antihypertensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…pilosa and C . citratus , bioactive compounds present such as the phytochemicals mainly flavonoids and phenolic compounds act synergistically to cause a reduction in cardiac output and/or total peripheral resistance and consequently a decrease in blood pressure [ 39 ]. These effects would therefore be one of the mechanisms by which the aqueous extract of the mixture exerts its antihypertensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested hypotensive mechanism of action of A. muricata extract is via the blockage of calcium ion channels, which lowers blood pressure [35]. Another study showed that A. muricata aqueous extract had antihypertensive properties; combinations of A. muricata and other plants, such as Persea americana, also exhibited antihypertensive activity, providing a safe and effective solution for hypertension prevention and treatment [95].…”
Section: Antihypertensivementioning
confidence: 99%
“…Research shows that the aqueous extract of Annona muricata and its combination products have hypotensive and antihypertensive properties, with the product combination causing synergism in administration. The combination is safe for use in hypertension, so it has promising therapeutic advantages for the prevention and treatment of hypertension (Sokpe et al, 2020). The next therapy is the gotu kola therapy which can reduce hypertension blood pressure.…”
Section: The Effectiveness Of Complementary Therapy In Hypertension B...mentioning
confidence: 99%